Acidic polymeric ionic liquids based reduced graphene oxide: An efficient and rewriteable catalyst for oxidative desulfurization - Zhang, Hairan; Zhang, Qian; Zhang, Ling; Pei, Tingting; Dong, Li; Zhou, Pengyu; Li, Chaoqi; Xia, Lixin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •A series of acidic catalysts based on rGO were designed for desulfurization.•Different acidic anions could be sequentially ‘written in’ and ‘erased’ on rGO.•Screening of catalysts could be achieved via the rewriteable cycle.•The interfacial desulfurization mechanism of acidic rGO was investigated.•Poly[ViEtIm][PW12O40]-rGO exhibits excellent catalytic performance and reusability. A new type of graphene-based catalyst with rewriteable function was designed and synthesized based on poly(1-vinyl-3-ethylimidazolium bromide) modified and reduced graphene oxide (denoted as poly[ViEtIm]Br-rGO). The modified polymeric ionic liquid poly[ViEtIm]Br not only acted as interlink between the polar catalytic anion and the non-polar graphene substrate, but also endowed the favorable dispersibility of poly[ViEtIm]Br-rGO in ionic liquid, leading to the adequate exposure of immobilized catalytic sites during the process of desulfurization. Moreover, due to the reversible anion-exchange property of the modified poly[ViEtIm]Br, various anions of Brønsted acids or heteropolyacids could be sequentially ‘written in’ or ‘erased’ on the nanosheets of rGO for desulfurization, thus establishing a green model for screening suitable catalysts based only on the limits of the same carrier. Such a rewriteable cycle was confirmed and monitored by characterization of TEM, FTIR spectroscopy and X-ray photoelectron spectroscopy (XPS). Based on this catalyst screening process of a rewriteable cycle, poly[ViEtIm][PW12O40]-rGO, a heteropolyanoin modified rGO, was selected as the optimized catalyst. Benefiting from the synergistic effects between rGO and acidic anions, together with the large surface area and open two-dimensional structure of rGO, poly[ViEtIm][PW12O40]-rGO was found to exhibit an excellent catalytic performance toward various sulfur-containing compounds. Furthermore, the outstanding reusability of poly[ViEtIm][PW12O40]-rGO was also displayed owing to its structural stability. It was found that the sulfur removal efficiency of DBT could still reach 98.0% after the catalyst poly[ViEtIm][PW12O40]-rGO had even been recycled eight times.